Penerapan IFRS Dan Pengaruhnya terhadap Keterlambatan Penyampaian Laporan Keuangan: Studi Empiris Perusahana Manufaktur di Bursa Efek Indonesia Periode Tahun 2008-2010 - Margaretta, Stepvanny; Soepriyanto, Gatot (Bina Nusantara University, 2012)
There are several factors that affect the companys delay in submitting the financial statements are often referred to as Audit Delay, among others IFRS (International Financial Reporting Standards), firm size, profitability, size public accounting firm, audit opinion, and complexity. One factor that is quite prominent is the application of IFRS that have not been uniform across all companies in Indonesia. It could also lead to Audit Delay. Firm size theoretically means companies bigger scale required to submit financial reports on time. As for profitability, KAP size, and complexity of the audit opinion is also decent enough to be considered as one of the influential factors on Audit Delay. The results of this study indicate that the application of IFRS, profitability, size KAP, audit opinion, and complexity does not have a significant impact on the delay for submission of financial statements. Finaly, a factor that leads to significant effect of time delay submission of financial statements is the size of the company.